Citizens' Attitudes, Knowledge, and Educational Needs in the Field of Omics Sciences: A Systematic Literature Review - Calabrò, Giovanna Elisa; Sassano, Michele; Tognetto, Alessia; Boccia, Stefania (Frontiers in Genetics, 2020)
Background The huge development of omic sciences is changing the classical medical approach and making new technologies available. In this context, education of citizens is essential to allow appropriate decisions about their own health. Hence, we aimed to summarize existing literature regarding citizens’ knowledge, attitudes, and educational needs on omic sciences. Methods We performed a systematic literature review (SLR) using Pubmed, ISI Web Of Science, and Embase databases. The eligibility criteria for inclusion in this review required that the studies investigated knowledge, attitudes, or educational needs regarding omic sciences among the general population. Results We included 54 studies, published between 2006 and 2020. Most of the included studies (72%) investigated citizens’ knowledge, half of them (56%) attitudes, and 20% educational needs in the field of omic sciences, while 52% investigated attitudes and perceptions about genetic and/or omic tests. Most studies (64%) reported a limited knowledge level among citizens, even though most (59%) reported participants understood the benefits of the use of omic sciences into medicine. As for omic tests, a controversial opinion towards their use into practice was reported among citizens. Most of the studies (82%) investigating citizens’ educational needs highlighted a clear gap to be filled. Conclusions Our SLR summarizes current knowledge on citizens’ literacy, attitudes, and educational needs on omic science, underlining the need for strengthening public engagement on this topic. Further research is needed, however, to identify appropriate methods and models to achieve such an improvement.